General solution to the decimal fraction of generalized fibonacci series - Ömür, Neşe,; Ulutaş, Yücel Türker, (Utilitas Mathematica, 2012)
In this study, we give general solution to the decimal fraction of the series whose coefficients are products of terms of sequences W n and X n. Various examples of our results are given.